Predator reduction with habitat management can improve songbird nest success. Issue 3 (12th March 2014) - White, Patrick J. C.; Stoate, Chris; Szczur, John; Norris, Ken
ABSTRACT Predation pressure on many threatened species, including European farmland songbirds, may have increased over recent decades. Predator reduction to protect declining bird populations is a controversial but potentially important tool for managers. Its effects require measurement before its consideration in conservation. Game management typically combines sympathetic habitat management measures with reduction of nest predators. It has been proffered as additionally benefiting farmland songbirds, but little is known about the effects on their demography. We analyzed 11 years of nest data from 6 songbird species on 3 lowland farms. The different game management regimes on the farms enabled us to test the hypotheses that systematic predator reduction (mammals and corvids) and sporadic corvid reduction improve nest success in songbirds. We detected a positive effect of systematic predator reduction on common blackbird (Turdus merula), common chaffinch (Fringilla coelebs), dunnock (Prunella modularis), song thrush (T. philomelos), and yellowhammer (Emberiza citrinella) but not common whitethroat (Sylvia communis). For the 5 species that demonstrated an effect, systematic predator reduction improved the odds of nests surviving a day within the nest cycle by a factor of between 1.59 and 1.89. For common blackbird, the effect occurred at the egg (laying and incubation) stage of the nest cycle, whereas for other species it occurred across stages. Sporadic corvid reduction had a positive effect on nest survival only for common blackbird (at the nestling stage only) and a negative effect only for yellowhammer (across both stages). The extent to which predator reduction might influence populations may depend on mechanisms such as re‐nesting compensation and overwinter mortality. Where habitat management is in place to assist threatened songbirds, intensive, systematic nest predator reduction may provide a useful conservation tool for improvement of nest success. © 2014 The Wildlife Society.